Tools Of Usul Al-fiqh In Realizing Maqasid Al-shari'ah In Sukuk Structure In Malaysia: An Initial Analysis - Muhammad Ridhwan Ab. Aziz; Mohd Shahid Mohd Noh (Contemporary Research Center, Australia, 2024)
Non-Indexed Publication